Current Challenges in Childbirth - Elito, Julio Jr (IntechOpen, 2023)
Current Challenges in Childbirth provides a comprehensive overview of childbirth. Chapters address such topics as induction of labor, labor progression, intrapartum care, uterotonics, care of the newborn, and more.